‘A fly in the ointment’ - Bahari, Norafida; Ab. Hamid, Suzana (UPM-MAKNA Cancer Research Laboratory, Institute of Bioscience, 2014)
The small endobronchial malignancies are rare entity that can cause obstruction of the major airways, causing symptoms such as dyspnoea, cough, haemoptysis and postobstructive pneumonia. The obstruction may lead to gradual asphyxiation. Case series of four patients: primary carcinoid, mucoepidermoid carcinoma and mixed squamo-adenocarcinoma are reviewed. This paper describes each of these cases including the clinical presentation, plain film at presentation, CT abnormalities and discusses the utility of CT in their diagnosis. Treatment and progression of disease also will be discussed.